2021
DOI: 10.1016/j.crgsc.2021.100087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of air pollutants in Covid 19 pandemic lockdown- a case study of Bareilly, UP, India

Abstract: The contemporary world is dealing with the rise of the novel coronavirus pandemic. Globally, as on 14 September 2020, there have been 28,918,900 confirmed cases of COVID-19, including 922,252 deaths, reported to WHO with the cases still on the rise. In India, as a preventive measure, complete lockdown was imposed all over the country from 25 th March, 2020 which has significantly reduced the vehicular movement. Bareilly was reported among the seven most air polluted cities of Uttar Prade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In addition, in another study carried out in Lahore, Pakistan, it was observed that as a result of the lockdown effect, even though the country recorded increasing COVID‐19 cases, the air pollution in the city reduces (Tauqir & Kashif, 2021 ). In another study conducted in India, the authors (Agarwal et al., 2021 ) observed that during the period of their study, vehicular movement was minimum as a result of COVID‐19 lockdown. In this study, they realised that the level of air pollutants; PM10, PM2.5, SO2 and NO2 were found to be 54, 41, 19, and 14 μg/m 3 , respectively which is minimum in the six months of study (January 2020–June 2020) and lowest in comparison to the air quality data of the last 25 years.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, in another study carried out in Lahore, Pakistan, it was observed that as a result of the lockdown effect, even though the country recorded increasing COVID‐19 cases, the air pollution in the city reduces (Tauqir & Kashif, 2021 ). In another study conducted in India, the authors (Agarwal et al., 2021 ) observed that during the period of their study, vehicular movement was minimum as a result of COVID‐19 lockdown. In this study, they realised that the level of air pollutants; PM10, PM2.5, SO2 and NO2 were found to be 54, 41, 19, and 14 μg/m 3 , respectively which is minimum in the six months of study (January 2020–June 2020) and lowest in comparison to the air quality data of the last 25 years.…”
Section: Resultsmentioning
confidence: 94%
“…In this study, they realised that the level of air pollutants; PM10, PM2.5, SO2 and NO2 were found to be 54, 41, 19, and 14 μg/m 3 , respectively which is minimum in the six months of study (January 2020–June 2020) and lowest in comparison to the air quality data of the last 25 years. The authors (Agarwal et al., 2021 ) came to the conclusion that as a result of lockdown which invariably reduces vehicular movement, there was a significant improvement in air quality across Bareilly in Uttar Pradesh, India. Furthermore, as observed in this study and many others, the role of COVID‐19 lockdown across various countries shows that anthropogenic and other factors, if they can be reduced, would greatly help in maintaining good air quality especially in urban centers (Rita et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 0.35 million deaths in 2019 were reported by UP as being related to air pollution, with 0.22 million of those deaths being due to ambient air pollution (AAP) and 0.11 million related to domestic air pollution [11]. According to several studies [13,14,15,16,17,18] household cooking, industrial operations, combustion of waste and the biomass, and congestion in traffic are the main causes of air pollution in UP.…”
Section: Introductionmentioning
confidence: 99%